2017
DOI: 10.4070/kcj.2016.0278
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Stents Coated with Artemisinin or Dihydroartemisinin in a Porcine Coronary Restenosis Model

Abstract: Background and ObjectivesArtemisinin and dihydroartemisinin are drugs used to treat malaria. These drugs suppress inflammatory reactions. The aim of this study was to examine the anti-intima hyperplasia effect of a novel drug-eluting stent with artemisinin or dihydroartemisinin in a porcine coronary restenosis model.Materials and MethodsPigs were randomized into four groups; in the first, the coronary arteries (20 pigs, a total of 40 coronary arteries, with 10 coronary arteries in each group) was implanted wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
3
1
0
Order By: Relevance
“…In addition, a recent study showing that the DHA-coated stent suppresses restenosis in a porcine coronary restenosis model (Jang et al, 2017) supports our findings.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In addition, a recent study showing that the DHA-coated stent suppresses restenosis in a porcine coronary restenosis model (Jang et al, 2017) supports our findings.…”
Section: Discussionsupporting
confidence: 90%
“…Taken together, our study provides data for the potential application of DHA in a drug‐eluting stent for the reduction of neointimal hyperplasia and restenosis after angioplasty. In addition, a recent study showing that the DHA‐coated stent suppresses restenosis in a porcine coronary restenosis model (Jang et al, ) supports our findings.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the other hand, as treatment experience has accumulated, drug repositioning of artemisinin is being actively attempted in various fields, including antiviral, antiparasitic, antifungal, anticancer, anti-immune, and anti-inflammatory activities. 6) In this issue of the Korean Circulation Journal , Jeong et al 7) reported the results of their investigation regarding the anti-arrhythmic effect of artemisinin. They used a canine experimental model of BrS induced by NS5806, an I to channel agonist.…”
mentioning
confidence: 99%